Facile Atomic‐Level Tuning of Reactive Metal–Support Interactions in the Pt QDs@ HF‐Free MXene Heterostructure for Accelerating pH‐Universal Hydrogen Evolution Reaction. Issue 22 (5th October 2021) - Pang, Sin‐Yi; Io, Weng‐Fu; Hao, Jianhua
Abstract: Supported metallic nanoparticles render highly tunable physical and chemical properties to mixed‐dimensionality materials in electrocatalysts. However, some supports are susceptible to being dissolved in acidic solution or are unstable in ambient air. The development of high‐performance catalysts has been facing the major hurdles of the sluggish activity in alkaline solution and requesting high energy to stabilize the nanoparticles on their supports, challenging the pH‐universality and the applicability of the supported metallic nanoparticles. Here, a one‐step strategy is proposed to modulate the growth of Pt quantum dots (QDs) on HF‐free MXene under atomic‐level by a low‐temperature metal–support interaction reaction. By controllable tailoring in the morphology and strain induced by terminations, Pt (111) QDs with a sub‐nanoscale size of 1.15 nm are grown as 0D/1D heterostructure to overcome the restrictions of employing reduction gas and high annealing temperature. The catalyst exhibits a low overpotential of 33.3 mV for acidic solution, while 65.1 mV for alkaline solution at a specific current density of 10 mA cm −2 . This study not only paves a scalable pathway to developing cost‐efficient catalysts in moderate conditions, but also demonstrates an effective surface modulation strategy for 0D/1D heterostructures. Abstract : Taking advantage of surface‐functionalized MXene and large surface area, a Pt QDs@MXene nanowire is fabricated by a facile method under moderate conditions and shortened synthesis time. After the two‐step transition process, a novel Pt@MXene (0D@1D) nanoheterostructure is formed and renders accelerated kinetics and exhibits a high hydrogen evolution reaction.